The importance of strigolactone transport regulation for symbiotic signaling and shoot branching - Borghi, Lorenzo; Liu, Guo-Wei; Emonet, Aurélia; Kretzschmar, Tobias; Martinoia, Enrico (Springer, 2016)
This review presents the role of strigolactone transport in regulating plant root and shoot architecture, plant-fungal symbiosis and the crosstalk with several phytohormone pathways. The authors, based on their data and recently published results, suggest that long-distance, as well local strigolactone transport might occur in a cell-to-cell manner rather than via the xylem stream. Strigolactones (SLs) are recently characterized carotenoid-derived phytohormones. They play multiple roles in plant architecture and, once exuded from roots to soil, in plant-rhizosphere interactions. Above ground SLs regulate plant developmental processes, such as lateral bud outgrowth, internode elongation and stem secondary growth. Below ground, SLs are involved in lateral root initiation, main root elongation and the establishment of the plant-fungal symbiosis known as mycorrhiza. Much has been discovered on players and patterns of SL biosynthesis and signaling and shown to be largely conserved among different plant species, however little is known about SL distribution in plants and its transport from the root to the soil. At present, the only characterized SL transporters are the ABCG protein PLEIOTROPIC DRUG RESISTANCE 1 from Petunia axillaris (PDR1) and, in less detail, its close homologue from Nicotiana tabacum PLEIOTROPIC DRUG RESISTANCE 6 (PDR6). PDR1 is a plasma membrane-localized SL cellular exporter, expressed in root cortex and shoot axils. Its expression level is regulated by its own substrate, but also by the phytohormone auxin, soil nutrient conditions (mainly phosphate availability) and mycorrhization levels. Hence, PDR1 integrates information from nutrient availability and hormonal signaling, thus synchronizing plant growth with nutrient uptake. In this review we discuss the effects of PDR1 de-regulation on plant development and mycorrhization, the possible cross-talk between SLs and other phytohormone transporters and finally the need for SL transporters in different plant species